PROCESSED PRODUCT DIVERSIVATION BASED COTTLE FISH FOR COASTAL FISHING COMMUNITIES: PROCESSED PRODUCT DIVERSIVATION BASED COTTLE FISH FOR COASTAL FISHING COMMUNITIES - Jamilah, Jamilah; Nurmala, Nurmala; Sullaida, Sullaida; Nadhiratun Nisa , Siti; Novita , Divia (RADJA PUBLIKA, 2022)
The highest production (catching) of tuna reached 32.22% per year but the selling price of fish was very low, while the fish processing business was only in the form of wooden fish (keumamah) and smoking due to low mastery of technology and absorption of innovation. The business of processing tuna into shredded fish and fish crackers has never been carried out by the coastal fishing communities of Aceh, even though this business has the potential to be developed on a household scale. The service activity aims to provide training on processing tuna into shredded fish and fish crackers for fishing communities in coastal areas in the category of poor families. The method used is the survey method and Focus Group Discussion (FGD). Demonstrations of processing tuna into shredded fish and fish crackers can open up insights and business opportunities for housewives and young fishermen in creating added value and profit for traditional fishing households as well as improving production management and marketing of competitively processed fish. This activity can foster an entrepreneurial spirit among coastal fishing communities to increase fishermen's household income.